Evaluación de los métodos de hidrólisis ácida, hidrólisis básica y extracción mecánica para la obtención de azúcares fermentables a partir de biomasa microalgal (2014)
The present work evaluates the obtaining of reducing sugars by (acid hydrolysis, base hydrolysis and ultrasonication) from biomass of Chlorella vulgaris. The respective microalgae grow is done with Foliagro cultivation medium, 0.2 VN and pH 6, with an agitation of 4L / min, 8 watt light intensity, 12 hours of light and 12 hours of darkness photoperiod and temperature between 23 ° C ± 3 ° C. Between the chemical and mechanical methods proven, the better results were obtained by acid hydrolysis, with 2N H2S04 concentration, using 0.5 9 of Iyophilized biomass, at temperature conditions of 120°C, pressure 1.2 bar, 30 min acid time exposure and neutralization with NaOH.